Room temperature routes towards the creation of zinc oxide films from molecular precursors - Gonzalez,Arellano DL; Bhamrah,Harley J; Yang,J; Gilchrist,JB; McComb; Ryan,MP; Heutz,SEM (ACS Omega, 2017)
The advent of “flexible” electronics on plastic substrates with low melting points requires the development of thin film deposition techniques that operate at low temperatures. This is easily achieved with vacuum or solution-processed molecular or polymeric semiconductors, but oxide materials remain a significant challenge. Here we show that zinc oxide (ZnO) can be prepared using only room-temperature processes, using the molecular thin film precursor zinc phthalocyanine (ZnPc), followed by vacuum ultra-violet light treatment to elicit degradation of the organic components and transformation of the deposited film to oxide material. The degradation mechanism was assessed by studying the influence of the atmosphere during the reaction: it was particularly sensitive to oxygen pressure in the chamber and optimal degradation conditions were established as 3 mbar with 40% oxygen in nitrogen. The morphology of the film was relatively unchanged during the reaction, but detailed analysis of itscomposition using both scanning transmission electron microscopy (STEM) and secondary ion mass spectrometry (SIMS) revealed that a 40 nm thick layer containingZnO results from the 100 nm thick precursor after complete reaction. Our methodology represents a simple route for the fabrication of oxides and multilayer structuresthat can be easily integrated into current molecular thin film growth setups,without the need for a high temperature step.